PENGARUH BERBAGAI METODE PENGUJIAN VIGORTERHADAP PERTUMBUHAN BENIH KEDELAI - Renan Subantoro; Rossi Prabowo (Universitas Wahid Hasyim, 2013)
Vigor is defined as a condition where healthy seed, when planted directly germinate quickly in different condition or potential groups of seeds to germinate fast, simultaneous and uniform then held a rapid growth in the general condition of the field. Old Seed will deteriorate. Symptom onset is only visible with a biochemical test or tress test. Continuing deterioration reduce the viability and vigor, even a poor crop performance though despite optimal environment. Experiments Paper Piercing Test is a test performed by germinating the seed vigor between the sand and filter paper. Germinated seed is old and new seed each totaled 50 seed to repeat 4 times, so there are 2 treatment on seed. Experiment Brick Gravel Test is a vigor test using shards of red brick as a medium for germination, with 2 soybean seed treatments, old and new, each amounting to 50 seeds with 4 replications. The results showed that: vigor testing showed that the higher seed vigor longer than the new seeds and media that generate the highest value for all parameters is brick gravel test, but the highest germination percentage achieved on paper piercing test. Key words : vigor, deterioration, brick gravel, paper piercing